USING “MOST NAMES”TO IMPROVE STUDENTS’ SPEAKING SKILL IN DESCRIPTIVE TEXT (The Action Research was Done to the Eight/A Grade Students of SMPN 1 Geger Madiun in the Academic Year 2012/2013) - Heny Sulistyo Rini (English Teaching Journal : A Journal of English Literature, Language and Education, 2013)
The research was done in August 2012 in SMPN 1 Geger Madiun. The subject of the study was the eight year students consisting of 20 students. It was a classroom action research. The researcher conducted the research in some steps for each cycle. There were planning, acting, observing, and reflecting. In collecting data, there were two kinds of data which were used in this study, the quantitative data and the qualitative data. The quantitative data were in the forms of students‟ scores. The data were students‟ scores from the beginning of the research to the end of the research. They came from the tests given. The qualitative data were collected by the following techniques: observations, interviews, and document analysis. The quantitative data were analyzed using descriptive statistics. It compares the score of the pretest to the score of the post test. The qualitative data were analyzed into data reduction, data display and conclusion drawing/ verification.The research findings showed that by implementing the “Most Names” in the speaking class, there were some improvements which can be classified into three main points as follow: The improvement of students‟ speaking skill; The improvement of students‟ participation; The improvement of students‟ interest; And the improvement of students‟ motivation. For that reason, “Most Names” was able to stimulate students to speak English.In conclusion, “Most Names” is able to improve students‟ speaking skill in class VIII/A.  However, “Most  Names” has  its  own  strength  and  weaknesses.  Most  Names stimulated students to be more active, interactive, and creative to speak English.In short, it is recommended to the teachers to use “Most Names” to improve the students‟ speaking skill in English.